(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
Summary: 1. The Challenges of Pluralistic Societies with Dissimilar Cultural Identities and Religious Traditions: from a Melting Pot to a Cultural Mosaic - 2. European Catholic Tradition of Dual Legislation and Jurisdiction: 2.1. The Development of the Religious Jurisdiction: from the Episcopalis Audientia under the Christian Roman Empire to the Homologation of Religious Decisions by a Civil Judge – 2.2. The Development of Secular and Religious Jurisdictions: from the Leges Barbarorum et Romanorum under the Principle of Personality to the Medieval Dual Jurisdiction in Europe – 2.3. Religious Minorities under Christian Rulers – 3. Muslim Legal Tradition of Plural Jurisdictions: 3.1. Muslim Empires and the Dhimma System – 3.2. Islamic Communities in Transition: from the Pre-colonial Era to the Colonial Rule – 3.3. The Exceptionality of Palestine and Israel- 4. Toward a Global World: Legal Pluralism and the Development of ADR. The Role of Religious Mediation and Arbitration: 4.1. The American Experience in Religious Arbitration: the Jewish Beth Din Courts and the Challenge of Islamic Arbitration – 4.2. Confronting the Fear of Islamic Arbitration Tribunals in the UK, Canada, and Australia - 5. Conclusions. Abstract: Most of juridical systems are historically developed from the interaction of two main legal principles: the principle of personality and the principle of territoriality. Roman Law is one of the best examples of it; its legacy channeled the growth and coexistence of religious and secular jurisdictions in the Germanic kingdoms of Western Europe. Under the principle of personality of laws, bonding individuals to their cultural or religious communities, legal pluralism was the common grounds from the Antiquity to the pre-Modern era. However, as a result of the religious wars in the Holy Roman Empire between Catholics and Protestants in the 16th and the 17th centuries, the Westphalian state model reinforced a territorial religious jurisdiction under the principle cuius regio eius religio, allowing the ruler to impose his religion on his subjects. The Muslim legal tradition developed, as well, plural juridical systems from the Dhimma System. One of them was the Ottoman Millet system that was adapted from the colonial era to the most of Middle East nation-states as a bonding personal religious law applied to non-Muslim communities. The secular paradigm of the Rule of Law, centralizing and reinforcing state and federal legislative powers, is implemented in Europe and her former colonies in the 19th century under the nation-state constitutional model, expanding worldwide the principles of territoriality and citizenship. As a result, religious legal systems are progressively confined to the private sphere. However, the secular paradigm is confronted gradually by a new development of legal pluralism, mainly as an effect of an extensive increment of global migrations; Halakha or Jewish Law, Canon Law or Catholic Law, Sharia or Islamic Law, are gaining strength as formal or informal religious ADR under the principle of Religious Freedom. Religious legal systems are becoming an innovative tool of mediation, conciliation, and arbitration accepted by some secular jurisdictions around the world, although there is a polarized debate about it. In today´s global world, which are the lessons to be learned from legal traditions and contemporary models of legal pluralism? Can religious legal systems become a tool of mediation for restorative justice preventing and exiting from violence? This article addresses this juridical and social challenge from an interdisciplinary comparative analysis.